The Right to Open Government: A Study within the Framework of Contemporary Constitutional Concepts - Jabbar Kraidi, Lect. Dr. Mohammad (Basra studies journal, 2023)
The concept of an open government refers to a government that shares its information with individuals, encourages their participation in decision-making, and provides mechanisms for holding the government accountable. This new constitutional concept is subject to continuous change, particularly as it navigates conflicting interests and is influenced by various factors, including the government’s own objectives in accessing information. Participation, transparency, and accountability remain fundamental goals of an open government. This right is one of the methods of governance that ensures individuals have access to documents and procedures of the executive and legislative branches, allowing effective oversight by individuals. Adopting this constitutional principle underscores a country’s credibility in respecting rights and freedoms. This right grants access to any information related to its humanitarian activities, covering all other rights.